L’etica nei procedimenti giudiziari - Indellicato, Michelle (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Ethics in judicial proceedings is a topic of considerable interest that has always sparked debate at the cultural level in general and at the ethical – legal level in particular. Ethics and law are not on different levels, but are interconnected. Judicial proceedings and all those involved in law enforcement cannot be separated from this interconnection and must be impartial, otherwise they undermine the dignity of a legal person and his fundamental rights, such as the right to truth, loyalty, justice, and a democratic and civil cohabitation for an orderly social life.